Corporate Social Responsibility Practices and Stakeholders’ Awareness: Case of Ethiopia - Kesto, Dakito Alemu; Ravi, Jaladi (American Journal of Trade and Policy, 2017)
The main aim of this review is to explore the corporate social responsibility practices and stakeholders’ awareness about firms’ CSR in Ethiopia. The concept of Corporate Social Responsibility (CSR) came into existence to show the responsibilities that the business should take from the shoulders of the government and the NGOs particularly in developing nations. Since the living standard of the society is low in emerging economies, the CSR expected from business firm is much higher than it is used to be in advanced economy. Ethiopia is one of the least developed countries and thus, the involvement of private sector is very crucial since government does not fulfill all needs of the society. In one way or another, businesses are economic entities that have the ability to change corporate social responsibility activities into business opportunities. Several studies suggest that companies may receive external benefits from implementing CSR policies. However, the success of practicing CSRs depends upon the level of stakeholders’ awareness. Specifically, in conducting the survey the reviewer was motivated by the following research questions which constitute the objectives of the article: (1) where do firms in Ethiopia categorized in the Carroll’s 1991 pyramid; and (2) what was the level of awareness of different stakeholders in the country. Therefore, this review explores the CSR practices of firms and the level of stakeholders’ awareness about the concept in Ethiopia. The paper employed qualitative research approach by reviewing 16 research articles which address CSR policies of firms in Ethiopia. The finding shows, the most important stakeholder considered by firms are customers which contribute to profitability. This shows the fact that firms in Ethiopia are in the lower-level of Carroll’s CSR pyramid: economic responsibility. Furthermore, the level of stakeholders’ awareness regarding the firms’ CSR practice in Ethiopia is low. To summarize, corporate social responsibility practice in Ethiopia is at its infancy stage and thus, need much more improvement from both firms and the government.